Differences In Creatinine Levels And Reticulocyte Values In CKD Patients Undergoing Epo And Non-Epo Therapy - Thomas Tandi Manu; Hikmatul Lailli; I Wayan Getas (Poltekkes Kemenkes Mataram, 2026)
Chronic kidney disease (CKD) is a condition of progressive and irreversible decline in kidney function. One of the main complications of CKD is anemia, caused by decreased erythropoietin (Epo) production by the kidneys. Epodi therapy is used to stimulate red blood cell production. Reticulocyte counts are used as an indicator of erythropoietic activity, while creatinine levels reflect the degree of kidney damage To determine the differences in creatinine levels and reticulocyte values between CKD patients undergoing Epo and non-Epo therapy.This study was a quantitative cross-sectional study. The sample consisted of 60 CKD patients, divided into two groups: 30 patients with Epo therapy and 30 patients without Epo therapy. Data were collected through medical records and analyzed using the independent T-test. The average creatinine level in the Epo group was 3.96 mg/dL, while in the Non Epo group it was 1.83 mg/dL. The average reticulocyte value in the Epo group was 0.64%, while in the Non Epo group it was 1.49%. The results of the independent T test statistical test obtained a P value of creatinine levels of 0.000_